STUDI MENGENAI PENGARUH TEKANAN WAKTU UNTUK MEMBELI, DERAJAT DIFERENSIASI PRODUK DAN CUSTOMER VALUE TERHADAP MINAT BERTRANSAKSI ULANG MENGGUNAKAN UANG ELEKTRONIK (Studi pada Pengguna Uang Elektronik e-Money di Kota Semarang) - Yulianto, Yana; Ferdinand, Augusty Tae; Soesanto, Harry (Master of Management Diponegoro University, 2016)
The pupose of this research is to build a customer value through time pressure to buy and the degree of product differentiation in improving interest in the use of electronic money transaction (Studies on users electronic moneye-Moneyin Semarang).Samples were the users electronic money in Semarang, a total of 102 respondents. Structural Equation Model (SEM) was run by AMOS software was used to analyze the data. The analysis showed that the customer value through time pressure to buy positive effect in improving interest in the use of electronic money transaction.The empirical findings indicate that time pressure to buy positive influence on improving interest in the use of eectronic money transaction, time pressure to buy possitive influence on cutomer value, the degree of product differentiation is not possitive effect on improving interest in the use of electronic money transaction, customer value possitive influence on improving interest in the use of electronic money transaction.